The Effect of CSR and Advertising on Purchase Decisions with Brand Awareness as a Mediation Variable on Consumers of AQUA Packaged Drinking Water Products (AMDK) in Salatiga City - Chandra Finata; Linda Kusuma (Budapest International Research and Critics University, 2022)
Every company has a goal to create big profits for the survival of the company by increasing sales. Some of the ways that companies usually do to influence consumer purchasing decisions include Corporate Social Responsibility (CSR) and advertisements about their products. In addition, the company's products are in great demand by consumers to create brand awareness of these products. This study uses quantitative methods that can be used to examine a particular population or sample. Based on the results of hypothesis testing, it can be concluded that Corporate Social Responsibility (CSR) and advertising have a positive effect on purchasing decisions. While brand awareness as a mediating variable can mediate advertising on purchasing decisions.